Trends of stratified prostate cancer risk in a single Korean province from 2003 to 2021: A multicenter study conducted using regional training hospital data - Ko, Young Hwii; Kim, Byung Hoon; Kwon, Se Yun; Jung, Hyun Jin; Hah, Yoon Soo; Kim, Yeon-Joo; Kim, Hyun Tae; Lee, Jun Nyung; Kim, Jeong Hyun; Kim, Tae-Hwan (Investigative and clinical urology, 2023)
To identify changes in prostate cancer (PCa) risk-stratification during the last two decades in Korea, where the social perception of PCa was limited due to a relatively low incidence but has recently been triggered by the rapidly increasing incidence of benign prostate hyperplasia. Retrospective data of patients who had received a diagnosis of PCa in a single Korean province (Daegu-Gyeongsangbuk) at all seven training hospitals in the years 2003, 2007, 2011, 2015, 2019, and 2021 were subjected to analysis. Changes in PCa risk-stratification were investigated with respect to serum prostate-specific antigen (PSA), Gleason score (GS), and clinical stage. Of the 3,393 study subjects that received a diagnosis of PCa, 64.1% had high-risk disease, 23.0% intermediate, and 12.9% low-risk disease. The proportion diagnosed with high-risk disease was 54.8% in 2003, 30.6% in 2019, but then increased to 35.1% in 2021. The proportion of patients with high PSA (>20 ng/mL) steadily decreased from 59.4% in 2003 to 29.6% in 2021, whereas the proportion with a high GS (>8) increased from 32.8% in 2011 to 34.0% in 2021, and the proportion with advanced stage disease (over cT2c) increased from 26.5% in 2011 to 37.1% in 2021. In this retrospective study, conducted in a single Korean province, high-risk PCa accounted for the largest proportion of newly registered Korean PCa patients during the last two decades and increased in the early 2020s. This outcome supports the adoption of nationwide PSA screening, regardless of current Western guidelines.